MERESPONS KONTROVERSIAL TOKOH: PENETAPAN HUKUM KHATIB PEREMPUAN DALAM FATWA MUI NO. 38 TAHUN 2023 - Fauzul Kabir; Hani Nadiya Putri; Fikri Tanjung; Ali Misran (Makkah: Journal Of Islamic Studies, 2026)
This article presents a normative-critical analysis of the Indonesian Council of Ulama (MUI) Fatwa No. 38 of 2023 concerning the permissibility of women serving as khatib in Friday prayer rituals. The fatwa was issued in response to public controversy sparked by religious statements allowing women to deliver Friday sermons before male congregations. Employing a qualitative normative approach, this study utilizes textual analysis, Islamic legal hermeneutics, and comparative fiqh methodologies. The primary data source is the official text of the MUI fatwa and its supporting documents, while secondary sources include the Qur’an, Hadith, classical and contemporary fiqh literature, and relevant scholarly works. The findings indicate that MUI prioritizes a bayānī (textual) approach, reinforced by qiyās, both verbal and practical ijmā‘, and istiṣlāḥī considerations aimed at preserving communal harmony. The study concludes that while the fatwa aligns with the dominant Sunni legal tradition, it also invites critical reflection regarding its methodological depth and its engagement with contemporary socio-religious dynamics and gender discourse.